Pengaruh Profitabilitas, Leverage, dan Ukuran Perusahaan Terhadap Pengungkapan Sustainability Report - Putry, Nur Anita Chandra; Meli, Marselina (Universitas Hamzanwadi, 2025)
Sustainability reporting disclosure is an important step in raising awareness of the social, economic and environmental consequences of companies. The purpose of this study is to determine the effect of profitability, leverage, and company size on the sustainability reports of mining companies listed on the Indonesia Stock Exchange in 2019 to 2023. Financial statements and corporate sustainability reports provide secondary data for this study. Ten samples were selected through purposive sampling, and various analysis methods, such as validity test, reliability test, classical test, and hypothesis test, were used. The test results show that profitability has a negative effect on sustainability report disclosure, while leverage and company size have a positive effect on sustainability report disclosure